PENGARUH KETERAMPILAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA BAWASLU PROVINSI MALUKU - Mainake, Christina; Aponno, Elsina Huberta; Tousalwa, Carla Caroline (Jurnal Administrasi Terapan, 2024)
This research aims to find out how work skills influence the work productivity of employees of the Maluku Province Election Supervisory Agency. This research was conducted because problems were discovered which showed that employees' work skills were inadequate in time management to carry out their duties. This will ultimately affect employee work productivity in terms of time and energy in the agency in general.This research is empirical research, with the entire population of employees at the Maluku Province Election Supervisory Agency. The data sample for this research consisted of 61 respondents, but only 56 respondents returned the questionnaire and were in the further data processing process. The analysis technique used is simple linear regression analysis. The research results show that work skills facilities have a positive and significant effect on the work productivity of employees of the Maluku Province Election Supervisory Agency. This means that the better the skills an employee has, the higher the employee's work productivity will be. Keywords: Work Skills, Work Productivity.